The Warsaw Ghetto Uprising striking a blow against the Nazis - Altman, Linda Jacobs (Berkeley Heights, NJ Enslow Publishers, Inc., 2012)
"Examines the Warsaw ghetto uprising, including the roots of the resistance in the Warsaw ghetto, stories from the participants in the uprising, how the battle ended, and how the small group of fighters became heroes during the Holocaust"--Provided by publisher.
Adam Czerniakow -- Mordechai Anieiewicz -- Yitzhak Zuckerman -- Zivia Lubetkin -- Simha Rotem -- Vladka Meed -- Marek Edelman -- Jurgen Stroop.
Includes bibliography references and Index
990L
Keywords: Holocaust, Jewish (1939-1945) -- Poland -- Warsaw; Jews -- Poland -- Warsaw -- History -- 20th century; Warsaw (Poland) -- History -- Warsaw Ghetto Uprising, 1943